Sports betting and the integrity of Australian sport: Athletes' and non-athletes' perceptions of betting-motivated corruption in sport. (March 2018) - Lastra, Reynald; Bell, Peter; Bond, Christine
Abstract: The purpose of this study is to gain a deeper understanding of betting-motivated corruption in Australian sport by exploring key stakeholders' perceptions. More specifically, it aims to discover the nature and perceived risks of betting-motivated corruption from the experiences of those within sporting organisations, and the effectiveness of anti-corruption strategies currently in place within Australian sport. Through a qualitative case study approach of three sites (sports) in Australia—rugby league, swimming and water polo—insight into the perspectives of 22 participants, namely athletes and non-athletes (coaches, support staff, administrators and referees) was gained through semi-structured interviews. Using the thematic analysis technique, patterns of themes were identified across the interview transcripts. The findings indicate that athletes and non-athletes view betting-motivated corruption and the involvement of transnational organised crime as non-existent within their sport. There were also mixed perceptions surrounding the effectiveness of current anti-corruption strategies in each sport. The paper provides a platform for future research and highlights the need for improvement in the anti-corruption strategies in place to prevent the threat of betting-motivated corruption on the integrity of Australian sport.